Promoting employee health through the creation of a neuropositive organisational and physical culture - Ulyanova, S.A.; Astafeva, O.V.; Limareva, Yu.A.; Fathutdinova, O.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to provide a theoretical basis for promoting employee health in companies using digital employee profiles based on building a neuropositive organisational culture and developing physical culture and sport. Methods and structure of the study. The empirical base was formed in the period from February to September 2025, data obtained during a pilot project in an educational organization (the total sample size is 15 employees). To assess neurophysiological and behavioral parameters, a psychometric and author’s questionnaire was used, including statements grouped on three scales: ‘Dopamine activity’ (motivation, initiative, goal orientation), ‘Oxytocin activity’ (trust, cooperation, sense of belonging), ‘Noradrenaline balance’ (stress tolerance, concentration, recovery after exertion). Results and conclusions. A systematic assessment of the level of neuroculture and the physical condition of employees through the creation of a digital profile of employees becomes a necessary condition for the formation of a neuropositive organizational environment and motivation of the team, which should include, among other things, caring for human health and providing opportunities for physical culture and sports, which will directly affect the neurophysiological mechanisms underlying motivation, engagement and stress resistance. The proposed neuropositive assessment system, through pilot studies or correlation analysis between sports involvement and the use of knowledge about neurophysiological responses to positive stimuli, simultaneously reflects the organizational culture and the level of physical well-being of employees through their involvement in corporate sports and activities.